ANALISIS DAN EVALUASI DAMPAK DANA ALOKASI KHUSUS TERHADAP INDIKATOR KINERJA PEMBANGUNAN DI DAERAH STUDI KASUS KABUPATEN-KOTA 2003-2013 - Nuryadin, Didi; Suharsih, Sri (Jurnal Ekonomi & Studi Pembangunan, 2017)
In the context of financial relations between the central and local governments, the central government has now allocated a Balancing Fund (Dana Perimbangan) to finance local needs in order to support the implementation of decentralization of governance and development as a form of political will to reform and democratize. The aim of this study is to evaluate the effectiveness of DAK allocation for financial year 2003-2013 and to analyze the impact of Dana Alokasi Khusus (DAK) allocation from 2003 to 2013 on various development indicators in the regions (districts / cities). DAK transfer design is the main cause of various issues related to the implementation of DAK. In addition, the problem of DAK allocation mechanisms in the determination of programs and activities, the calculation and use of DAK, budgeting and disbursement of DAK, reporting and monitoring and evaluation of DAK. DAK, as one type of Balancing Fund, has a positive impact on the fiscal capacity of the region, especially the district /city. In addition to regional fiscal capacity, DAK also plays a role in reducing the level of fiscal gap between districts / cities during the period 2003-2007. The result show that DAK allocation (in total) is not significant influence to PDRB per capita of Regency / City. In conclusion, DAK has not had a significant impact on public services and public welfare. This is because the direction of using DAK is not directly used to "build", but only to "maintain". Therefore, DAK is considered not effective enough in an effort to achieve the national priority target.